Conjunction Selection Errors in the Speech of a Three-Year-Old Child - Angela, Nofia; Boesriswati, Endry; Rafli, Zainal (KnE Social Sciences, 2023)
This study used a grammatical cohesion device to identify the conjunction selection errors in the speech of a 3-year-old girl named Noura Inayah. The research identified how children choose the most appropriate conjunctions to improve literacy, particularly in a three-year-old. A descriptive-qualitative method was used as the research approach. The words used by the child when narrating or telling stories were recorded. Besides accuracy errors, the child also made conjunction selection errors. This is consistent with Gleason’s theory that at the developmental stage, a child can combine two sentences into one, but conjunction selection errors would be frequent. Parents are expected to have an essential role in developing their children’s language, such as by using reading and writing activities for early childhood. Keywords: Grammatical Cohesion, Conjunction, Emergent Literacy